Program Pendidikan Pemakai Di Perpustakaan Pascasarjana Universitas Muhammadiyah Sumatera Utara - Diana Maulida Zakiah; Fithria Rizka Sirait; Ernita Siagian (Universitas Sari Mutiara Indonesia, 2023)
This study aims to find out how the user education program at the Postgraduate Library of the University of Muhammadiyah North Sumatra, including user education materials, methods used, challenges and obstacles. The research method used is descriptive qualitative, with interview techniques with 2 informants, namely librarians. The results showed that the user education program at the Postgraduate Library of the University of Muhammadiyah North Sumatra was carried out online and ran quite well, there were several supporting and inhibiting factors. Factors that hinder the program are difficult schedule determination, network constraints at student locations, and there is no written policy or guidebook about the program